Management of Physical Education and Adaptive Health Learning at Extraordinary Elementary School in The Entire Metro City of Lampung (Journal of Physical Education and Sports, 2019)
This study is the learning management of physical education and adaptive health at Extraordinary Elementary Schools in the entire Metro city of Lampung. The purpose of this study is to analyze planning, implementation, evaluation, and not the results of the evaluation of learning physical education and health adaptive in Extraordinary Elementary Schools in the entire Metro city of Lampung. This type of research is qualitative. Data collection techniques used observation, interviews, and documentation. The results of the study on lesson plan made by teachers at Extraordinary Elementary Schools throughout Metro city of Lampung has followed the provisions of the curriculum, the teacher also made syllabus and lesson plan, but the teachers didn’t analyze the learning materials yet. The implementation of learning is following the implementation stage of learning, namely opening, core activities, and closing. The way that teachers use in learning evaluation is different, considering the characteristics experienced that different for each students, one of the activities carried out by teachers in learning evaluation is give feedback after completion of the core activities, while the results of follow-up evaluation of learning conducted by teachers enrichment or remedial as one form of follow-up results of an assessment of physical education teaching sports and adaptive health in the metro city of Lampung. In accordance with the results of the study, it is expected that teachers and managers at school can apply the learning process by using learning management efficiently, and effectively by paying attention to several points in the series of learning processes which consist of planning, implementation, evaluation, and follow-up of learning evaluation results especially on physical education and adaptive health.